Handbook for Integrated Soil Fertility Management - Fairhurst, Thomas (CABI, 2012)
This ISFM handbook is organized into seven sections that include: an introduction, the need for ISFM, the principles of ISFM, soil fertility management practices, targeting ISFM options, an introduction to soil and crop production and a section containing tables, definitions and reference information. The entire project team that includes the TAG hopes that the reader finds this handbook a useful tool for tackling soil fertility and management on the continent and elsewhere where similar factors of production are at play.